Representação social de velhice e de cuidado entre cuidadores ocupacionais de idosos - Ziesemer, Nadine de Biagi Souza (2017)
The general objective of this study was to apprehend the social representations that elders’ home caregivers have about caring and old age. And the specific objectives tried to profile the research participants, as well as the practices that they develop when caring for older adults, reflecting on how such practices are influenced by the conceptions of old age and caring represented by the participants. Therefore, its theoretical and methodological trajectory was grounded in the theory of social representations, proposed by Serge Moscovici, and in the content analysis, oriented by Laurence Bardin. A qualitative, quantitative descriptive research study was carried out with 50 caregivers of older adults, who develop their activities at home settings in the city of Curitiba, Brazil. Participants were contacted by means of the “snowball” technique, in which one interviewed subject recommends the other. For data colllection, a structured questionnaire with closed and open questions was used. Quantitative analysis was carried out in the sociodemographic and in the work/labor profile of the participants. As for the quali-quantitative analysis, oriented to the linguistic-discursive material related to old age, it was structured in axes and subaxes regarding the research objectives. The results evidenced that 92% of the participants were female, mean age of 47.7 years (SD=10.7 years), 76% graduated from high school, and 50% attended the initial and ongoing training course on caregiving to older adults. Among the caregivers with less than ten years in this job, caregiving-course attendance was significantly higher than the ones who were working in this context for over 10 years. Mean time in that job was 9.0 years (SD=9.6 years). The occupation is informally performed by 52% (no register in the Labor Card), and mean working hours add up to 50.6 weekly hours (SD=15.5 hours), with a salary of up to two minimum wages for 64% of them. 90% exclusively care for older adults, performing household tasks complementary to caring. In general, they started this activity due to the market demand, as well as their interest in caring for the elderly, with 38% migrating from sectors like industry and commerce, and 34% from other activities of housekeeping itself. In relation to the initial and ongoing training course on elderly caregiving, data comparison between participants who attended and those who did not attend those courses, pointed that their qualification did not foster better work conditions, regarding their labor rights or salaries. The axis Representation of the old age unfolded contradictions expressed by mixed positive and negative enunciations of the aging process, with slight prevalence of positive objectifications. Among them, it can be pointed out temperament traits, wisdom ideals, independence, autonomy, health and affection. Among the negative ones, difficulties in relationship, physical/body decay, denial of the old age, dependence, suffering and disease. The axis Representation of caring contemplated objectifications related to affective aspects in its three investigated subaxes. Finally, the axis Practices of caring for the old age pointed out, among caregivers’ favorite activities, the communicative and affective ones, totaling 50% of the enunciations. In addition, among their disliked practices, 57% referred to technical procedures, such as elderly mobility and human excreta-related hygiene. In the final considerations of the study, it is possible to assume that social representations of old age and caring influence participants’ practices, which are developed with brief emancipatory trend, anchored in the paradigm of active aging, largely addressed in national and international public policies. It was evidenced that research involving aspects related to the profile of caregivers of older adults and their representations of caring and old age, as well as their working practices, is still insipient in Brazilian and international settings. In that sense, data from this current study portray a reality that may contribute to other studies concerned with this theme, and it may ground the design of training courses to those professionals